Developing Specific Chinese Teaching Material for Indonesia Based on a Comparation between Chinese and English Teaching Materials - Rosalin, Kelly (Bina Nusantara University, 2013)
Teaching material is a foundation of language learning. It is also a very important tool in teaching and learningÂ process. Especially for students who learnt in non-Chinese environment, during the learning process, they can only rely on teachers and teaching materials. Article was based on previous research about teaching methods. Article used two teaching materials that have Indonesian language translation Contemporary Chinese and Chuji Biaozhun Huayu. Besides, it compared the content and designed to analyze the similarities and differences of these teaching materials. Through the analysis, research gives solution in teaching materials design.